A game-based learning approach to sleep hygiene education: a pilot investigation - Seaver, Christine; Bowers, Clint; Beidel, Deborah; Holt, Lisa; Ramakrishnan, Sridhar (Frontiers in Digital Health, 2024)
Sleep hygiene education (SHE) consists of environmental and behavioral practices primarily intended to reduce sleep problems. Currently considered ineffective as a stand-alone treatment, the manner in which the education is typically delivered may be ineffective for the acquisition of new knowledge. The purpose of this study was to determine if a more engaging teaching medium may improve the efficacy of sleep hygiene education. This study examined the use of gamebased learning to teach SHE to individuals with sleep problems. Participants had significant improvements in sleep quality and state anxiety after using the app for 30 days, although scores for the majority of patients remained elevated. This pilot investigation provides initial evidence for the efficacy of a game-based approach to SHE.